A novel Tiki-Taka algorithm to optimize hybrid flow shop scheduling with energy consumption - Mohd Fadzil Faisae, Ab Rashid; Muhammad Ammar, N. M. (Faculty of Engineering, Khon Kaen University, 2022)
Hybrid flow shop scheduling (HFS) has been thoroughly studied due to its significant impact on productivity. Besides the impact on productivity, the abovementioned problem has attracted researchers from different background because of its difficulty in obtaining the most optimum solution. HFS complexity provides good opportunity for researcher to propose an efficient optimization method for the said problem. Recently, research in HFS has moved towards sustainability by considering energy utilization in the study. Consequently, the problem becomes more difficult to be solved via existing approach. This paper modeled and optimized HFS with energy consumption using Tiki-Taka Algorithm (TTA). TTA is a novel algorithm inspired by football playing style that focuses on short passing and player positioning. In different with existing metaheuristics, the TTA collected information from nearby solution and utilized multiple leaders’ concept in the algorithm. The research began with problem modeling, followed by TTA algorithm formulation. A computational experiment is then conducted using benchmark problems. Then, a case study problem is presented to assess the applicability of model and algorithm in real-life problems. The results indicated that the TTA consistently was in the first and second ranks in all benchmark problems. In addition, the case study results confirmed that TTA is able to search the best fitness solution by compromising the makespan and total energy utilization in the production schedule. In future, the potential of TTA will be further investigated for flexible hybrid flow shop scheduling problems.